Effect of Methyl Jasmonate Combined with Calcium Chloride Treatment on Storage Quality of Dictyophora rubrovalvata - Chao MA; Tongjie CHEN; Jiang LIU; Guangxian CHEN; Duanpu WU; Erjuan XU; Rui WANG (Shipin gongye ke-ji, 2023)
The aim of this study was to investigate the effects of combined treatment of methyl jasmonate and calcium chloride on storage quality of Dictyophora rubrovalvata. The Dictyophora rubrovalvata was used as the experimental material in this experiment, and the effects of different dealing methods (preharvest distilled water spray treatments mark CK, preharvest 3% calcium chloride spray (S1), preharvest 0.3 mmol/L methyl jasmonate spray (S2), preharvest 0.3 mmol/L methyl jasmonate+3% calcium chloride spray (S3)) on the storage quality of Dictyophora rubrovalvata at (1±0.5) ℃ were studied. The results showed that compared with CK group, the different treatment groups could inhibit the increase of weight loss rate and respiratory intensity, reduce the Dictyophora rubrovalvata shearing force, malondialdehyde content, maintain the free amino acid content, protein content, polysaccharide content and flavone content, and maintain the SOD, CAT and POD activity of the Dictyophora rubrovalvata. At 12 d of storage, the decay rate of Dictyophora rubrovalvata in CK, S1, S2 and S3 groups was 32.56%, 28.32%, 19.85% and 14.64%, and the weight loss rate was 5.62%, 3.89%, 2.89% and 2.21%. In general, methyl jasmonate combined with calcium chloride could significantly delay the deterioration process of Dictyophora rubrovalvata and the decline of its storage quality. Therefore the combination of spraying methyl jasmonate combined with calcium chloride before picking had the best fresh-keeping effect, which could maintain the storage effect of Dictyophora rubrovalvata. This study can provide theoretical reference and technical support for the preservation of Dictyophora rubrovalvata.